2013
DOI: 10.5504/bbeq.2013.0086
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Mycoviruses Related to Geminivirus Isolated from the Soil-Borne FungiMacrophomina Phaseolina(Tassi) Goid. andMucor RacemosusBull

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Mycoviruses are currently classified into 23 families and one unclassified genus ( Figure 1 ) by the ICTV according to their genome type and organization; (accessed on 27 March 2023). The majority of mycoviruses studied to date have dsRNA or ssRNA genomes, however, a few mycoviruses with ssDNA genomes have also been found [ 12 , 52 , 53 , 175 , 328 ].…”
Section: Diversity and Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Mycoviruses are currently classified into 23 families and one unclassified genus ( Figure 1 ) by the ICTV according to their genome type and organization; (accessed on 27 March 2023). The majority of mycoviruses studied to date have dsRNA or ssRNA genomes, however, a few mycoviruses with ssDNA genomes have also been found [ 12 , 52 , 53 , 175 , 328 ].…”
Section: Diversity and Taxonomymentioning
confidence: 99%
“…ssDNA mycoviruses are not exclusively found in Genomoviridae , however. For example, geminivirus-like ssDNA has also been discovered in Macrophomina phaseolina (M. phaseolina DNA virus; MpDV) and Mucor racemosus (M. racemosus DNA virus; MrDV) [ 53 ]. Additionally, a novel ssDNA mycovirus, Gigaspora circovirus A has also been discovered and belongs to the Circoviridae family but has not yet been assigned to the genus [ 52 ].…”
Section: Diversity and Taxonomymentioning
confidence: 99%
“…In a recent study, Myers et al (2020) found 27.1% of the 107 Mucoromycota fungi screened by cellulose chromatography or transcriptome-mining positive for mycoviruses [8]. Previously, virus-like particles (VLPs) were detected in five Rhizopus isolates [9], a geminivirus-like ssDNA virus was described in Mucor racemosus [10], and a (−) ssRNA virus was detected in Mucor irregularis [11]. Recently, four viruses with dsRNA genomes were detected and characterized in Umbelopsis ramanniana [7], and two (+) ssRNA narnaviruses were reported from Rhizopus microsporus [12].…”
Section: Introductionmentioning
confidence: 99%
“…named as Mucorales RNA virus 1 (MucRV1). In addition, a geminivirus-like ssDNA virus was described and characterized in Mucor racemosus (Hafez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%